Strategic alignment of corporate sustainability and financial performance : Insights from Europe’s top-performing companies across sensitive and non-sensitive industries - Nikkilä, Hanna (My University, 2025)
This thesis delves into the contemporary issue of whether it pays off to behave well. A company's sustainability practices can be seen through its commitment to the triple bottom line (TBL) and environmental, social, and governance (ESG) principles, reflected in measurable outcomes as evidenced by ESG scores. Sustaining competitive advantage requires companies to adapt to evolving legal standards and place greater emphasis on ESG practices. ESG is nowadays a critical and common component in companies’ strategies. Europe seeks to become the first carbon-neutral continent by 2050 under the European Union (EU) Green Deal, necessitating companies to adopt and further develop their ESG frameworks. Companies can embed ESG into their strategies in different ways, thereby complying with EU Green Deal goals and fulfilling the EU Corporate Sustainability Reporting Directive (CSRD). Advancing ESG practices has little strategic relevance unless it aligns with favorable financial outcomes. This thesis examines how high ESG-performance companies align their strategies to implement ESG practices without compromising financial performance. The intense interest in the association between ESG performance and corporate financial performance (CFP) has attracted numerous studies; however, the evidence remains mixed. Prior research has mainly focused on the US market or worldwide, giving the European market minimal attention. Similarly, industry specification has not yet gained much popularity. This thesis explicitly addresses the European market, focusing on the EU, Switzerland, and Norway, and paying special attention to sensitive and non-sensitive industries, as well as the ESG-CFP relationship of top- performing companies. To address the laid premises, an unbalanced panel data set of 1254 companies is used, and a fixed-effect regression is applied to analyze data from 2016 to 2023. This thesis provides valuable insights into the interrelation between ESG and CFP and finds a significant and positive association between companies’ ESG performance and profitability, measured as long-term operating performance using an accounting-based indicator, return on assets (ROA). Overall, in the sample, no positive link was found between ESG and CFP. Positive findings were observed in sensitive industries. Indicating that ESG performance does enhance financial performance. When studying individual pillar associations with CFP in a non-sensitive industry, when focusing solely on the EU-market environmental performance, a positive, significant correlation was found. It was found that top-performing companies’ strategies excel when assessed against ESG commitment indexes, contributing to their high ESG performance. Consistent with stakeholder theory, the findings indicate that stakeholders reward substantial ESG commitments, enhanced risk mitigation, and more favorable debt- financing terms.

Tämä opinnäytetyö käsittelee ajankohtaista kysymystä siitä, kannattaako yritysten panostaa vastuullisuuteen. Yrityksen kestävän kehityksen käytännöt näkyvät sen sitoutumisessa kolmoistilinpäätökseen sekä ympäristöön, yhteiskuntaan ja hyvään hallintotapaan (ESG), jotka heijastuvat mitattavissa olevina tuloksina, ESG-pisteissä. Tutkimus keskittyy ESG-pisteisiin sekä kestävässä kehityksessä parhaiten suoriutuvien yritysten strategioihin. Kilpailuedun ylläpitäminen edellyttää yrityksiltä sopeutumista muuttuviin lakisääteisiin standardeihin sekä yritysvastuuseen, mikä pitää sisällään ympäristövastuun, sosiaalisen vastuun ja hyvän hallintotavan. ESG on nykyään kriittinen ja yleinen osa yritysten strategioita. Eurooppa pyrkii ensimmäiseksi hiilineutraaliksi mantereeksi vuoteen 2050 mennessä Euroopan unionin (EU) vihreän siirtymän mukaisesti, mikä edellyttää yrityksiltä ESG-viitekehysten omaksumista. Yritykset voivat sisällyttää ESG-tekijät strategioihinsa eri tavoin ja siten saavuttaa EU:n vihreän siirtymän tavoitteet ja täyttää EU:n yritysvastuuraportointidirektiiviä (CSRD). ESG-käytäntöjen edistämisellä on vain vähän strategista merkitystä, ellei se ole linjassa suotuisten taloudellisten tulosten kanssa. Tämä opinnäytetyö tarkastelee, kuinka korkean ESG-suorituskyvyn yritykset yhdenmukaistavat strategioitaan ESG-käytäntöjen toteuttamiseksi vaarantamatta taloudellista suorituskykyään. ESG-käytäntöjen ja yritysten taloudellisen suorituskyvyn (CFP) välisen yhteyden tutkiminen on herättänyt kiinnostusta, mutta näyttö on edelleen ristiriitaista. Aiempi tutkimus on keskittynyt pääasiassa Yhdysvaltojen tai maailmanlaajuisiin markkinoihin, antaen Euroopan markkinoille vain vähän huomiota. Samoin toimialakohtainen tarkastelu ei ole vielä saavuttanut suosiota. Tämä opinnäytetyö käsittelee nimenomaisesti Euroopan markkinoita, keskittyen EU:hun, Sveitsiin ja Norjaan sekä kiinnittäen erityistä huomiota ympäristösensitiivisiin ja ei-sensitiivisiin toimialoihin sekä parhaiten suoriutuvien yritysten ESG-CFP- suhteeseen. Tutkimus kohdistui epätasapainoiseen aineistoon 1254 yrityksestä, joiden vastuullisuus toimien ja taloudellisen tuloksen välistä yhteyttä tutkittiin kiinteävaikutusmallin avulla vuosien 2016–2023 aikana. Tämä opinnäytetyö tarjoaa arvokasta tietoa ESG:n ja taloudellisen suorituskyvyn välisestä vuorovaikutuksesta. Tulokset viittaavat merkittävään ja positiiviseen yhteyteen. Tätä yhteyttä tarkastellaan kirjanpidolliseen, pitkän aikavälin operatiivisen suorituskyvyn, omaisuuden tuotto (ROA) avulla. Positiivisia tuloksia havaittiin ympäristösensitiivisillä toimialoilla. Tämä osoittaa, että ESG-suorituskyky parantaa taloudellista suorituskykyä sensitiivisillä toimialoilla. ESG voidaan jakaa sen kolmeen eri osa-alueeseen. Tutkittaessa yksittäisten osa-alueiden yhteyttä CFP:hen, ei-sensitiivisellä toimialalla, huomioiden ainoastaan EU-maiden yritykset, ympäristökäytännöt osoittivat positiivisen ja tilastollisesti merkitsevän yhteyden. Havaittiin myös, että korkean ESG-suorituskyvyn yritysten strategiat mahdollistavat erinomaisen ESG- käytänteet. Sidosryhmäteorian mukaisesti havainnot osoittavat, että sidosryhmät palkitsevat merkittäviä ESG- sitoumuksia, tehostettua riskienhallintaa ja suotuisampia velkarahoitusehtoja.
Keywords: Environment, social and governance responsibility, green deal, corporate financial performance, corporate social responsibility, corporate sustainability reporting directive, triple bottom line, ympäristövastuu, sosiaalinen vastuu, hyvät hallintotavat, yritysvastuu, yrityksen taloudellinen suorituskyky, vihreä siirtymä, kolmoistilinpäätös, yritysvastuuraportointidirektiivi